Key performance indicators for value management implementation in construction industry - Abd. Kadir, Muhammad Adam (2013)
Today, Value Management (VM) is an approach that has been widely used by various industries in managing their projects or programs to get the best value. In reaping the advantages of the VM implementation, Malaysia is no exception to implement the VM in construction projects, especially for projects carried out by the government. Therefore, the implementation should be implemented properly so that the implementation objectives can be achieved. To ensure the implementation of the VM is implemented well, the performance of its implementation should be measured. Various methods have been introduced to measure the performance of the work and one of them is the implementation of the Key Performance Indicators (KPIs). KPIs implementation has been widely used in measuring the performance of a project or work processes. Due to this reason, research is conducted to identify the trends of VM implementation in the construction industry in Malaysia, and then formulate the KPIs to measure the performance of its implementation. To achieve that purpose, a set of 187 questionnaires were distributed to the selected respondents to get their opinion on the VM and the implementation of KPIs to measure the performance of the VM in the Malaysian construction industry. The frequency analysis and average index showed that all 47 of the proposed have been agreed by the respondents. However, the obtained results are merely meant as a guide to identify KPIs for the implementation of VM in the Malaysian construction industry. The selection and screening of these KPIs should be conducted again to see the interest of each KPI in the projects undertaken